Assessment of the Incidence and Associated Risk Factors of Urinary Tract Infection among children- A Retrospective studyAssessment of the Incidence and Associated Risk Factors of Urinary Tract Infection among children- A Retrospective study (Medico Legal Update, 2020)
A study to assess the Incidence and Associated Risk Factors of Urinary Tract Infection among children atselected tertiary care hospital, Kanchipuram District, Tamil Nadu. The objectives is to determine the incidenceof UTI among children, estimate the types of bacteria causes UTI among children with UTI, to estimatethe incidence of urinary tract infection among children.and find out the Association between the UTI andselected risk factors of children. The convenience sampling was used to 50 paediatric medical records fromJanuary 2017 to December 2018. The data collection tool was validated and reliability was established. Thedata were collected by structured questionnaire. The collected data was tabulated and analysed. Descriptiveand Inferential Statistical method were used. The study shows that the higher frequency of 0-6 years (58%)and the lower frequency 13-18 years (18%). In Gender, Male is the highest frequency (56%) and Female isthe lowest frequency(44%) and the history of birth defect of structure/deformity or blockage in one of theorgan (20%), Vesico Ureteral Reflux (60%), Pelvic uretero junction (10%), Exstrophy of bladder system(10%). The highest frequency Vesicoureteral Reflux (60%) and the lowest frequency is Pelvic ureterojunction (10%) and exstrophy of bladder system (10%). It is found that E.coli (86%), Klebsiella (10%),Proteus (2%), Pseudomonas (2%). The highest frequency E. Coli (86%) and the lowest frequency Proteus(2%), Pseudomonas (2%) most causative organism of UTI. The incidence rate for urinary tract infection inour study was 11.7%. There was a significant Association between the selected demographic variables andrisk factors of UTI.